2001
DOI: 10.1046/j.1365-2567.2001.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of complement regulators in the conjunctiva and within the eye leads to massive inflammation and iritis

Abstract: SUMMARYThe open environment of the eye is continuously subject to an in¯ux of foreign agents that can activate complement. Decay-accelerating factor (DAF), membrane cofactor protein (MCP) and CD59 are regulators that protect self-cells from autologous complement activation on their surfaces. They are expressed in the eye at unusually high levels but their physiological importance in this site is unstudied. In the rat, a structural analogue termed 5I2 antigen (5I2 Ag) has actions overlapping DAF and MCP. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Animals subsequently develop posterior segment inflammation, with evidence of retinal vasculitis, vitreitis, and retinal and subretinal inflammatory infiltrates (Caspi et al, 1988). Activation of the complement system is involved in the pathogenesis of EAU (Bardenstein et al, 2001, Marak et al, 1979, Read et al, 2005, Sohn et al, 2000) as evidenced by the marked reduction in severity of disease when C3, the central component of the complement cascade, is deleted or inhibited by treatment with the soluble regulatory protein sCrry (Read, Szalai, 2005). However, which of the complement anaphylatoxin receptors mediates the pro-inflammatory effects of complement during EAU remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Animals subsequently develop posterior segment inflammation, with evidence of retinal vasculitis, vitreitis, and retinal and subretinal inflammatory infiltrates (Caspi et al, 1988). Activation of the complement system is involved in the pathogenesis of EAU (Bardenstein et al, 2001, Marak et al, 1979, Read et al, 2005, Sohn et al, 2000) as evidenced by the marked reduction in severity of disease when C3, the central component of the complement cascade, is deleted or inhibited by treatment with the soluble regulatory protein sCrry (Read, Szalai, 2005). However, which of the complement anaphylatoxin receptors mediates the pro-inflammatory effects of complement during EAU remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…21 Activation of complement can lead to the formation of a membrane attack complex responsible for complement cytolytic activity against cells that do not express the adequate regulatory proteins. Unregulated complement activation has been involved in the pathogenesis of conjunctival inflammation, 22 ocular infections, 23 anterior uveitis, 24,25 iris necrosis, 22 diabetic retinopathy, 26 proliferative vitreoretinopathy, 27 as well as in drusen formation and age-related macular degeneration. 28,29 Additionally, proteolytic cleavage of native complement proteins generates anaphylatoxins that bind to specific receptors on nearby cells and induce the release of pro-inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this theory, Bardenstein et al . [31] showed that blocking the complement regulator CD59 in the rat eye precipitated massive inflammation in the anterior eye, including intense conjunctival inflammation and iritis. Our evidence that complement pathway components and regulators are highly expressed in anterior segment tissues provides further impetus for investigating their links to ocular disease.…”
Section: Resultsmentioning
confidence: 99%